Administrative law: text and materials / by Mark Elliott, Jack Beatson and Martin Matthews - Beatson, Jack. (New Delhi, 2005)
To many, if not all, readers of this book, private law will be a familiar notion. Private law refers to such branches of the law as contract and tort, and is concerned principally with the duties and obligations which individuals owe to one another. Now, it is, of course, possible for government and other public bodies to enter into contracts and to engage in conduct which may be tortious; when they do, they are, quite rightly, in general regulated by the same body of private law as citizens. However, it is clear that, in addition to doing things, such as breaching contracts and carelessly causing injury, that can readily be dealt with by private law, government and public bodies commit a wide range of acts that cannot meaningfully be so regulated. Consider, for instance, the position of an individual whose house is to be compulsorily purchased and demolished by government to make way for a new airport, or an asylum-seeker who is told that he must leave the country. Many of the issues which arise in such circumstances cannot adequately be regulated private law. Does the government, in the first place, possess the legal power to order the purchase and destruction of the house? Would it make a difference if the government had decided to site the airport in a particular location for self-serving party political reasons eg to create jobs in a nearby marginal constituency? Should the asylum-seeker have been given an opportunity- and, if so, what sort of opportunity- to plead his case before the decision to deport him was taken? Can the asylum-seeker be deported to a particular country if there is evidence to suggest that he would be treated inhumanely or tortured upon arrival there? Questions such as these are peculiarly relevant to the type of powers exercised by government and public bodies, and a separate body of law to regulate the exercise of such powers therefore required.
Keywords: Administrative law